Malignant Gastric Glomus Tumor: A Case Report and Literature Review of a Rare Entity - Zaidi, Shaesta (Oman Med J, 2016)
A glomus tumor is a mesenchymal neoplasm that usually develops in the peripheral soft tissue, especially in the distal part of the extremities. The subungual zones of the fingers and toes are the most frequent sites of observation. The majority of glomus tumors are entirely benign, and the malignant counterparts are very rare, especially those arising in the visceral organs. We report a case of an extremely rare malignant glomus tumor arising in the stomach of a 53-year-old female admitted to the King Khalid University Hospital, Saudi Arabia. The patient reported a four-month history of pain and fullness in the left hypochondrium. She underwent laparotomy and resection of the gastric mass. The mass was analysed by histopathology. Based on the pathological findings of large tumor size, nuclear atypia, increased mitotic rate, atypical mitosis, the presence of necrosis, and characteristic immunohistochemistry the diagnosis of malignant glomus tumor was rendered. Ultrastructural study confirmed the diagnosis. The patient is well and continues regular follow-up.